Perhitungan Harga Pokok Pesanan dengan Pendekatan Metode Full Costing - Alfian Sayuti; R. Ayu Ida Aryani; Defel Septian (PT Seval Literindo Kreasi, 2022)
In 2022, the MSME sector needs to increase its operational activities due to the declining economy due to the pandemic, so that company profits can be improved. Companies in the manufacturing sector have more complicated activities than in the trade or service sector. This will affect manufacturing business actors in measuring manufacturing costs, cost of goods manufactured, and cost of goods sold accurately based on a measurable cost accounting approach. Based on this, descriptive qualitative research was conducted to compile the cost of goods ordered at a manufacturing company in Babakan, Mataram. The results showed that there were differences in the calculation of the cost of goods ordered between the company's calculations and the researchers' calculations. This difference is because the company does not charge asset depreciation in the order cost. This could be because the company did not record its assets so the depreciation expense could not be determined.